Understanding agroecological livestock paths in northern Uruguay - Rivaben, Inés Ferreira; Rossi, Virginia; Chia, Eduardo (Sustainability in Debate, 2023)
Agroecology is emerging in Uruguay as an alternative production model. Understanding and interpreting the vision of farmers and rural technicians on the agroecological transition processes in the country is a challenge for research. The main hypothesis that motivated this study is that the views of producers and technicians on agroecology guide, frame, and structure the transition processes. This article presents the results of two focus groups carried out in 2020 with professionals from different institutions and family livestock farmers in the north of the country. They show the great diversity of visions and the different paths taken by farmers. Despite these different visions, some common ideas could contribute to defining an agroecological livestock farming model. These paths permit suggesting and evaluating differentiated proposals for developing agroecological family farming.